Method for producing pellets
By mixing organic hydrogel binder with the granular substrate to form stable pellets, the stability and consistency of powder binder in the production of pellets is solved, and a stronger and more efficient pellet production is achieved.
Patent Information
- Application Number
- CN202380056442.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-28
- Filing Date
- 2023-07-27
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, when producing pellets, powder binders are difficult to process into stable and solid forms, and there are problems of material losses, safety hazards and inconsistent production, especially in industrial-scale production.
The organic binder is mixed with water to form an organic hydrogel binder and mixed with the particle substrate. By standing, the binder forms a hydrogel around the particles, thereby forming a clump.
Through the use of hydrogel binders, the processability and consistency of the pellets have been improved, reducing machine load and overheating, and the pellets produced are stronger, have higher strength and rigidity, reducing the need for subsequent heating, and have significant environmental and economic benefits.
Smart Images

Figure CN119731353A_ABST
Abstract
Description
[0001] The present invention relates to methods for producing pellets, in particular iron-containing pellets, from a particulate substrate and a hydrogel binder, and to the pellets obtained using these methods.
[0002] Although abundant in the Earth's core, the amount of carbon and various metals and metal ores available is limited. There are environmental costs associated with mining metal ores and metals such as iron and smelting activities, particularly in terms of pollution. It is therefore desirable to maximize the recovery of waste materials, which in turn reduces the waste that must be processed and stored, for example, in the case of iron waste, typically by long-term storage in heaps or pools.
[0003] The production of pellets from granulated iron ore and other metal ores is generally known in the art. Typically, such pellets are bound together using a binder to form pellets. During the pelletizing process, the binder is typically added as a powder. However, the powder may be difficult to process into pellets in a stable and sufficiently strong form that can be transported not only to the point of use but also within a large processing plant at its destination. The powder binder may also explode or easily escape into the atmosphere. This may be economically disadvantageous due to the loss of material and may be dangerous because the powder in the atmosphere may be inhaled.
[0004] In addition, the pelletizing process using powders often gives inconsistent results and may be problematic when production is scaled up due to the difficulty of effectively dispersing powders in industrial-scale mixers. As a result of the effects of temperature and pressure, interference may also exist between the binder components. The use of powders may also affect dissolution differences in an unpredictable manner. This means that a large amount of testing is required before industrial-scale use, making the transition from formulation to industrial pelletizing more difficult and expensive.
[0005] It would therefore be desirable to develop a process for pelletizing in which the pellets have improved ease of manufacture without loss of strength and stability.The present invention aims to overcome or ameliorate at least some aspects of this problem.
[0006] Therefore, in a first aspect of the present invention, there is provided a method for producing pellets, the method comprising the steps of: mixing an organic binder with water to form an organic hydrogel binder; mixing the hydrogel with a particulate substrate selected from metal ore, waste containing metal ore, metal fines, iron slag, iron filings, mineral waste, carbonaceous material, electric arc furnace waste or a combination thereof to form a substrate mixture; and forming agglomerates.
[0007] In a second aspect of the present invention, a method for producing pellets is provided, the method comprising the steps of: providing a wet particulate substrate selected from metal ore, waste containing metal ore, metal fines, iron slag, iron filings, mineral waste, carbonaceous material, arc furnace waste or a combination thereof; mixing the wet particulate substrate with an organic binder to form a wet substrate mixture; allowing the wet substrate mixture to stand so that a hydrogel of the organic binder is formed around the particulate substrate; and forming agglomerates.
[0008] In a third aspect of the present invention, there is provided a pellet obtained by the method of the first aspect or the second aspect of the present invention, which comprises a particle substrate selected from metal ore, waste containing metal ore, metal fines, iron slag, iron filings, mineral waste, carbonaceous material, electric arc furnace waste or a combination thereof and an organic hydrogel binder.
[0009] The method according to the first aspect and the second aspect of the present invention allows the binder to be dispersed more effectively by the particle substrate in the final pellet product. Without being bound by theory, it is believed that the formation of hydrogel by an organic binder not only bonds the substrate particles together, thereby enhancing the strength of the final pellet, but also acts as a processing aid, because in the form of a hydrogel, the binder is more dispersible, and therefore can have a lubricating effect. In general, this improves the processing of the pellet, causing more consistent results. In addition, in an industrial scale mixer, the hydrogel binder is more easily dispersed than the powder binder. Therefore, this causes improved efficiency by reducing machine load and overheating. In addition, it has been unexpectedly found that, relative to the equivalent composition without gelation, the final pellet produced in the method of the present invention is more solid, has higher strength and rigidity, which reduces the demand for subsequent heating (for example, drying or curing process) after the production of the pellet to stabilize it for storage, transportation and use. This has significant environmental benefits, because it requires less energy to produce pellets with sufficient strength from granular material, and process efficiency is introduced, because cold pelletization can be completed quickly, without the need for heating equipment or the absence of the delay that may be caused by another heating stage. Furthermore, the pellets obtainable by the method according to the first or second aspect of the invention generally also exhibit high thermal stability, which means that the pellets are reduced to carbon at a controlled rate and do not disintegrate in a furnace.
[0010] Typically, the particle substrate is selected from metal ore, waste containing metal ore, metal fines, iron slag, iron filings, mineral waste, carbonaceous materials, electric arc furnace waste or its combination. Usually, the particle substrate is selected from metal ore, waste containing metal ore, metal fines, iron slag, iron filings, carbonaceous materials, electric arc furnace waste or its combination. The particle substrate is usually derived from waste products of other industrial processes. The particle substrate can include waste products from a single waste stream (wherein there will be only changes in particle size) or from waste products from a combination of waste streams (wherein there will be mixed wastes of different compositions). This is environmentally beneficial because the recovery and reuse of such materials reduces the amount of limited resources that may otherwise be wasted.
[0011] The carbonaceous material can be coke, graphite, carbon black, peat, or coal. Typically, the carbonaceous material will include coke and / or coal. As used herein, the term "coal" is intended to include lignite, sub-bituminous coal, bituminous coal, steam coal, and anthracite. Coke has been found to be particularly problematic in forming pellets, and therefore the present invention provides particular benefits in providing more robust coke pellets.
[0012] Mineral waste may include mill scale, mill mud, fines from ore and / or metal-containing waste.
[0013] Without wishing to be bound by theory, it is believed that whether the particulate substrate comprises a single waste material type or a combination of different waste material types, the use of a gel binder aids in the distribution of the waste material in the pseudomatrix prior to curing to form a mass.
[0014] The metal may be, or the metal ore mineral waste may comprise: iron, zinc, nickel, copper, chromium, manganese, gold, platinum, silver, titanium, tin, lead, vanadium, cadmium, beryllium, molybdenum, uranium, aluminum or mixtures thereof; or a single metal, or in the form of, for example, an oxide or silicate. Typically, the metal will be a transition metal, such as iron, zinc, nickel, copper, chromium, manganese, gold, platinum, silver, titanium, tin, lead, vanadium, cadmium, molybdenum, aluminum or mixtures thereof, but the metal may also be uranium.
[0015] Typically, the particle substrate comprises a metal, and more typically, the particle substrate comprises iron. The use of iron is advantageous due to its easy availability, and because it can be reused and recovered from waste products of other processes to provide environmentally sustainable accessibility to such materials. Where the particle substrate comprises a metal ore, the ore will typically be an iron ore, such as goethite, limonite, siderite, taconite, hematite, or magnetite. Typically, where the particle substrate is a metal ore, it will be an iron ore, such as hematite or magnetite.
[0016] The particle substrate can be a powder or metal chips, the term "metal chips" being given its usual meaning in the art. Typically, the particle diameter of the particle substrate is 4 mm or less (widest axis). Typically, the particle diameter will be in the range of 30 μm to 4 mm, typically 50 μm to 3 mm or 0.1 mm to 2 mm. Typically, at least 10% by weight of the particle substrate is able to pass through a 100 μm sieve before being formed into pellets. The presence of a range of particle sizes within the sample improves the accumulation of material within the agglomerate during extrusion. The term agglomerate uses its usual meaning in the art, i.e., a granular material formed by a collection of particles that are physically or chemically bound together.
[0017] Typically, the particulate substrate is added in an amount of about 70% to about 99.9% by weight of the pellets, preferably about 80% to about 99% by weight, and more preferably about 90% to about 95% by weight.
[0018] Auxiliary binders may also be present, so that the binder used in the described methods may comprise one or more organic binders, or a combination of an organic binder and one or more auxiliary binders. Typically, the binder is present in the pellets in a range of about 0.05 wt % to about 4 wt %, usually in a range of about 0.5 wt % to about 4 wt %, and usually in a range of about 0.5 wt % to about 2.5 wt %.
[0019] The advantage that organic binder has is that it can be used at low concentrations, and therefore will not significantly affect the metallurgy or physical properties of the substrate mixture. Organic binder can be added in powder form, gel form or other pre-dissolved forms (that is, organic binder is in liquid suspension). In the example where organic binder is added as powder, water will be present to promote the in-situ gelation of organic binder. Relative to liquid addition, providing organic binder as powder or gel allows good control of the total water content of pellets. Allowing organic binder to form gel (before or after being added to substrate) improves the cold strength of pellets, reduces or eliminates the demand for long heating or drying process and the energy input required for such process. If organic binder does not form hydrogel, but instead for example takes the form of film, such advantage may not exist. An example of the situation where organic binder forms film can be when the amount of water in mixture is limited, causing less dissolution of organic binder in water, thereby preventing hydrogel from forming.
[0020] Typically, the organic binder is selected from an organic resin (e.g., a polyacrylamide resin), a cellulosic material (e.g., carboxymethyl cellulose (CMC), hydroxyethyl cellulose (HEC), or hydroxyethyl methyl cellulose (MHEC)), a polyvinyl alcohol (PVA), a phenolic resin (e.g., a resol, which is a base-catalyzed phenolic resin having a formaldehyde to phenol ratio greater than one, typically about 1.5, or a novolac resin having a formaldehyde to phenol molar ratio less than one), and / or a polysaccharide (e.g., a starch, such as wheat starch, corn starch, barley starch, and potato starch; gum arabic, guar gum, or xanthan gum). Typically, the organic binder is selected from an organic resin, a cellulosic material, a polyvinyl alcohol, and / or a phenolic resin.
[0021] In the case where the organic binder is a cellulosic material, it is generally carboxymethyl cellulose (CMC). CMC is advantageous because it can be added in powder form, which allows the total moisture content of the pellets to be controlled. CMC also has a longer shelf life than organic binders from other plant sources. This is because organic binders from other plant sources are more susceptible to microbial attack, and are therefore more likely to decompose. Sometimes, the organic binder can be hydroxyethyl methylcellulose (MHEC), which has been found to have particularly good bonding qualities, and helps to enhance the strength of the pellets. However, since MHEC is highly water-soluble, this may affect the shelf life of the final pellets, shortening the shelf life compared to the pellets comprising CMC.
[0022] Typically, the organic binder includes carboxymethyl cellulose (CMC), polyacrylamide, phenolic resin, polyvinyl alcohol (PVA), or a combination of these organic binders with each other or with other organic binders such as those listed above. Alternatively, the organic binder may consist essentially of one or more of CMC, polyacrylamide, phenolic resin and / or PVA; consist of CMC, polyacrylamide, phenolic resin and / or PVA; or consist of only one of CMC, polyacrylamide, phenolic resin and / or PVA, such as CMC or PVA.
[0023] Typically, CMC can be used as an organic binder instead of or in addition to other organic binders, such that the organic binder can contain about 10 wt % to about 100 wt %, typically about 20 wt % to about 90 wt % or about 50 wt % to about 75 wt % CMC. Where the organic binder contains CMC, it is typically added in the range of about 0.01 wt % to about 1.5 wt % of the pellet, typically about 0.1 wt % to about 1 wt % of the pellet.
[0024] Typically, when in solution, the CMC organic binder has an active polymer content of about 40% to about 90% and a pH in the range of about 5 to about 9, or about 6 to 8. In addition, the molecular weight of the CMC will generally be in the range of about 3,000 to about 70,000. Optionally, the molecular weight of the CMC will generally be in the range of about 10,000 to about 50,000. Without being bound by theory, it is believed that at lower CMC molecular weights, such as in the range of about 10,000 to about 50,000, a highly concentrated organic binder solution can be prepared, which in turn can improve the strength of the pellets.
[0025] Typically, the organic binder includes polyvinyl alcohol (PVA). PVA can be used as an organic binder to replace other organic binders or in addition to other organic binders, so that the organic binder can include about 10% by weight to about 100% by weight, usually about 20% by weight to about 90% by weight or about 50% by weight to about 75% by weight of PVA. When the organic binder includes PVA, it is typically added in the range of about 0.01% by weight to about 1.5% by weight of the pellet, usually about 0.05% by weight or 1% by weight to about 1% by weight of the pellet.
[0026] Without being bound by theory, it is believed that PVA provides fast curing and high strength because the polymer network formed by PVA is strong. In addition, the process of pelletizing with PVA removes air from the bulk material, which can reduce oxidation of the substrate, which is metal. Metal oxidation is undesirable for the simple reason that it reduces the amount of metal (e.g., metallic iron) available for processing by the end user.
[0027] Polyvinyl alcohol is typically formed commercially from polyvinyl acetate by replacing the acetate radicals of the acetate with hydroxyl radicals by reacting the polyvinyl acetate with sodium hydroxide in a process known as saponification. Partial saponification means that some of the acetate groups have been replaced with hydroxyl groups, thereby forming an at least partially saponified polyvinyl alcohol residue.
[0028] Typically, the degree of saponification of PVA is at least about 80%, typically at least about 5%, at least about 90%, at least about 95%, at least about 99% or about 100% saponification. PVA is commercially available from, for example, Kuraray Europe GmbH in Germany. Typically, it is used as a solution in water. PVA can be modified to include, for example, sodium hydroxide content.
[0029] Typically, when in solution, the PVA organic binder has an active polymer content of about 12% to about 13% and a pH in the range of about 4 to about 7. In addition, the molecular weight of the PVA will generally be in the range of about 15,000 to about 150,000. Optionally, the molecular weight of the PVA will generally be in the range of about 30,000 to about 120,000. Without being bound by theory, it is believed that, for example, at lower molecular weights in the range of about 15,000 to about 60,000, a highly concentrated organic binder solution can be prepared, which in turn can improve the strength of the pellets.
[0030] In the case where the organic binder is a polysaccharide, it can be starch or amylase starch. For example, it can be pregelatinized potato starch. It can be added in an amount of about 0.8% by weight of the final pellet, preferably about 0.6% by weight. It may be desirable to use a polysaccharide as an organic binder because polysaccharides also usually act as thickeners.
[0031] The organic binder (alone or in combination with one or more auxiliary binders) can be present in a range of about 0.05% to about 1.5% by weight of the pellet. Typically, in a range of about 0.07% to about 1.0% by weight, or about 0.1% to about 0.9% by weight. It has been found that in the presence of less than about 0.05% by weight of the organic binder, the structural integrity of the agglomerate is low.
[0032] In the method of the first aspect of the invention, an organic binder is mixed with water to form an organohydrogel binder.
[0033] As used herein, the term "hydrogel" means a material that is not a liquid that flows easily and is not solid, but a gel composed of a gel-forming material (e.g., a hydrophilic polymer that is insoluble in water). In other words, a hydrogel can be a semisolid substance. Typically, a hydrogel is formed by a gel-forming material, such as a hydrophilic polymer, that forms an interconnected cross-linked network that can trap, absorb, and / or otherwise retain water, thereby producing a gel. Some hydrogels can be diluted with other liquids, such as water, that break the interconnected network to produce a solution, although typically the hydrogel of the present invention will be a cross-linked hydrogel that does not dissolve when diluted.
[0034] Typically, the amount of water in the hydrogel is in the range of about 1 wt % to about 5 wt %, or about 2 wt % to about 4 wt %, or about 2.5 wt % to about 4.5 wt %, or about 3 wt %. Without being bound by theory, it is believed that not all of the water mixed with the organic binder prior to addition to the substrate is present in the final hydrogel. This is because a small amount is used to ensure that other components are dissolved or mixed.
[0035] The formation of the organohydrogel binder may take a time in the range of about 20 minutes to about 2 hours, preferably about 30 minutes to about 1 hour. The time taken to form the organohydrogel binder may be varied by factors such as additional processing, temperature (typically in the range of about 10°C to about 60°C, or about 15°C to about 40°C, or about 20°C to about 30°C for optimal solubilization), grade selection of CMC, grade selection of iron ore, and mixing. At these temperatures, it was found that the pellets formed were particularly strong relative to pellets of the same formulation but not processed via gel formation.
[0036] In the method of the second aspect of the invention, the standing of the wet substrate mixture allows the formation of a hydrogel of the organic binder around the particulate substrate. As used herein, the term "standing" or "acidification" is given its ordinary meaning in the art, i.e., wherein the wet substrate mixture is left for a sufficient period of time without external disturbances such as heating, shearing or mixing to allow the organic binder and the particulate substrate to form a hydrogel.
[0037] Without wishing to be bound by theory, as above in relation to the first aspect of the invention, it is believed that not all of the water associated with the wet substrate is present in the final hydrogel. This is because a small amount is used to ensure that other components are dissolved or mixed.
[0038] Typically, the ratio of organic binder to particle substrate is from about 0.1% to about 0.8% organic binder to about 99.9% to about 99.2% particle substrate, preferably from about 0.15% to about 0.5% organic binder to about 99.85% to about 99.5% particle substrate.
[0039] The wet substrate mixture is left to stand so that the hydrogel of the organic binder formed around the particle substrate may spend the time in the following scope: about 5 minutes, 15 minutes or 30 minutes to about 2 days, usually 1 hour to 1 day (i.e. 24 hours) or less than one day, for example 9 hours, 6 hours or 3 hours. The required time depends on the property of selected binding agent. Usually, the time of standing is in the scope of 15 minutes to about 2 hours, particularly when there is an auxiliary binder. For example, cellulosic material forms gel after standing for several hours (for example 15 minutes to 3 hours, or 1 hour to 2 hours) usually. However, organic resin and phenolic resin can be usefully allowed to stand for a long time, for example 3 hours to 2 days, or 6 hours to 1 day.
[0040] The method of the present invention may further comprise the step of adding an auxiliary binder to the substrate mixture.The substrate mixture may be the dry substrate mixture of the first aspect of the present invention or the wet substrate mixture of the second aspect of the present invention.
[0041] The secondary binder forms a bond with the particulate substrate, such as iron ore, which allows the final pellets to withstand the heat and pressure during transportation to the furnace.
[0042] Typically, the auxiliary binder comprises an inorganic binder. The inorganic binder may include one or more silicates (e.g., silicates in the form of their sodium salts); or refractory materials, including but not limited to oxides, carbides, or nitrides of silicon, aluminum, magnesium, calcium, and zirconium, and combinations thereof.
[0043] For example, the refractory material may include alumina, fire clay, bauxite, chromite, dolomite, magnesite, silicon carbide, zirconium oxide, or a combination thereof. As used herein, the term "refractory material" refers to a material that resists thermal stress, high pressure, or corrosion by chemical agents.
[0044] Typically, the inorganic binder includes one or more silicates. Typically, the inorganic binder includes two to four different silicates. One or more silicates can be in liquid form, powder form, or a combination thereof. Possibly, the auxiliary binder is in powder form.
[0045] Typically, the inorganic binder (alone or in combination with one or more organic binders) is present in the pellets in a range of about 0.5 wt % to about 2.5 wt %, typically about 1 wt % to about 2 wt %, or about 1.25 wt % to about 1.75 wt %.
[0046] When silicates are present, and one or more silicates are in liquid form, they will generally be present in larger amounts due to the lower activity levels in liquid silicates compared to powdered silicates. Where one or more silicates are in liquid form, they are generally present in the pellets in a range of from about 0.5% to about 2.5%, typically from about 1% to about 2%, or from about 1.25% to about 1.75% by weight.
[0047] Where the one or more silicates are in powder form, they are typically present in the pellets in a range of about 0.5 wt % to about 2.5 wt %, typically about 1 wt % to about 2 wt %, or 1.25 wt % to about 1.75 wt %.
[0048] The method of the present invention may further comprise the step of adding one or more further additives to the substrate mixture.
[0049] As mentioned above, the hydrogel formed with the organic binder can serve as a processing aid. The method of the present invention can also optionally include the step of adding a separate processing aid to the substrate mixture. Processing aids include, but are not limited to, dilute solutions of cationic polymers, anionic polymers, or nonionic polymers, typically based on acrylic acid flocculants, carbon (usually in the form of graphite), lubricants, surfactants (e.g., sodium lauryl sulfate), stearates (e.g., calcium stearate or sodium stearate), stabilized fibers, or combinations thereof. Processing aids can make the entire process more efficient, which in turn saves both cost and energy.
[0050] The step of forming the pellets may include extruding the mass. The extrusion process may be carried out at a temperature in the range of about 30°C to about 70°C, typically about 35°C to about 55°C. In addition, the process may be carried out at atmospheric pressure or under vacuum. As used herein, the term "under vacuum" takes its usual meaning in the art, as the extrusion process may be carried out at a pressure below atmospheric pressure.
[0051] The step of forming the pellets may include cold forming the agglomerate. The term "cold forming" means, for example, that there is no solidification, sintering or heating to above about 60°C or above about 40°C or about 30°C. In other words, it may be the case that only low levels of heat will be applied if there is application of heat during agglomerate forming. In addition, when the agglomerate is pelletized, although friction heat may be generated by any pressing and / or extrusion process used, and the binder may undergo an in-situ exothermic reaction, this may sometimes be the only heat applied. It is expected that these inherent heating mechanisms will not generate heat sufficient to affect the formation of the pellets.
[0052] Alternatively, it may be the case that low levels of heat are applied, such as heating in the range of about 100°C to about 250°C. Low levels of heating allow pellets to form faster, and may be in the range of about 100°C to about 250°C, or generally in the range of about 150°C to 200°C. When low levels of heating are applied, they may be applied for a period of time in the range of about 1 minute to about 24 hours. The application of heat generally promotes the drying and curing of the pellets, thereby ensuring that they are ready for transportation and use when needed. The skilled person will understand and appreciate that factors such as the external ambient temperature, the nature of the components in the formulation, and the desired characteristics of the pellets to be produced (e.g., low moisture content) will affect whether external heat is required, the level of heat applied, and how long the time period lasts. Therefore, the skilled person will consider such factors when determining the time period in the process and the level of heat applied, for example, providing an environment of about 30°C to 50°C (based on the external ambient temperature or heating) for 6 hours to 24 hours or 9 hours to 18 hours may be conducive to pellet formation. Alternatively, heating for shorter periods of time, such as 1 minute to 3 hours, or 15 minutes to 100 minutes, in the range of 125° C. to 175° C. may be desirable. Thus, the briquettes, and then the pellets, may be cold formed or formed with the application of a low level of heating such that they will be formed at a temperature in the range of about 10° C. to about 250° C., or about 15° C. to about 200° C., or about 20° C. to about 150° C.
[0053] The advantages of cold forming or forming with only low levels of heat in terms of reduced energy consumption relative to the hardening manufacturing techniques commonly used are significant. High temperature furnaces are also not required to produce the pellets, resulting in a simpler and more economical and environmentally beneficial manufacturing process.
[0054] Conventionally, a thermal process is used to form pellets, thereby producing so-called thermally bonded (hardened) compacts. In the hardening technology, initially, a "green" pellet is formed by a combination of a particle substrate and a binder, and then it is formed into a pellet (usually using a pelletizer). As used herein, the term "green pellet" adopts its usual meaning in the art, and refers to a pellet that does not yet have the strength required for its final use and requires further treatment or processing. The green pellet is hardened via a series of steps including drying, preheating, firing and cooling of the green pellet. Water is removed in a controlled manner to prevent crack formation and maintain the structural integrity of the pellet. The temperature range of the drying stage depends on the chemical and physical properties of the green pellet; however, it may last for 5 minutes to 10 minutes in the range of 100°C to 250°C. The preheating stage is generally carried out using a tilted heating process from about 300°C to 350°C for 10 minutes to 15 minutes, up to about 1250°C to 1350°C. The preheating stage ensures that any metal hydrates or metal carbonates present are decomposed into their anhydrous forms. The decomposition of these types of compounds helps to improve the structural integrity of the resulting pellets by removing water and / or gases (which may react during firing, resulting in overpressure and rupture of the pellets). The firing stage will typically be carried out at a temperature greater than 1350°C for about 10 minutes to 20 minutes (for typical capacities, such as 250tph to 500tph), and will result in the sintering of the pellets, thereby providing the strength required to make them suitable for their final use. During the sintering process, the bonding within the pellets is formed by recrystallization and bridging, resulting in ceramic bonding and the formation of large voids, which allows some expansion and stress relief. As used herein, the term "large voids" is associated with voids within the pellets, and the size range of the diameter is about 50μm to about 1mm. Void formation is particularly important in the case where the briquette is a metal ore briquette, because the reduction of the metal (such as the conversion of hematite to magnetite in iron ore) causes volume changes and stresses on the briquette. Since large void formation does not occur without firing, alternative methods are needed to prevent the disintegration of the pellets when placed under internal stress. The gelation technology described herein provides such an alternative by offering improved chemical bond strength.
[0055] In addition, relative to the method of the present invention, hardening processes are uneconomical because they are complex, must be carefully performed, and require the application of a large amount of heat. For example, the preparation of raw materials is crucial. In order to withstand the process, the components of the raw pellets must have a suitable size range, surface area and moisture content, because surface chemistry plays an important role. In addition, since the process involves multiple heating stages, it requires a large amount of energy. Therefore, a pellet production method that is less energy-intensive and more cost-effective is needed. In addition, such a method is needed, in which there is greater flexibility in the physical state of the particulate material used, and it leads to the production of pellets with physical properties comparable to or even superior to those produced using the hardening method. The method of the present invention helps to provide a solution to this problem through the use of its hydrogel binder.
[0056] In the method according to the second aspect of the invention, the wet granular substrate may contain water in the range of about 1 wt% to about 40 wt%, preferably about 3 wt% to about 25 wt%, more preferably about 5% to about 15%.
[0057] The pellets obtained by any of the methods of the first and second aspects of the invention may be cold formed or formed by low level heating (eg in a temperature range of 10°C to 250°C).
[0058] Typically, the average volume of the pellets according to the third aspect of the invention is between 2.5 cm 3 Up to 15cm 3 Within the range, usually within 3cm 3 Up to 12cm 3 , or 7cm 3 Up to 11cm 3 The pellets will generally be sized to minimize surface area and will generally be, for example, generally spherical, oval, cylindrical, or cubic in structure.
[0059] Unless otherwise stated, each of the described integers may be used in combination with any other integer as would be understood by a person skilled in the art. Furthermore, while all aspects of the present invention preferably "comprise" the features described in relation to that aspect, it is specifically contemplated that they may "consist of" or "consist essentially of" those features outlined in the claims. Furthermore, unless specifically defined herein, all terms are intended to be given their meanings as commonly understood in the art.
[0060] Furthermore, in the discussion of the present invention, unless stated to the contrary, the disclosure of an optional value for the upper or lower limit of the allowed range of a parameter should be interpreted as an implicit statement that each intermediate value between the lower optional value and the larger optional value of the parameter is itself also disclosed as a possible value for the parameter.
[0061] In addition, unless otherwise indicated, all numerical values appearing in this application should be understood as being modified by the term "about". The term "weight %" and similar terms are intended to mean the percentage of the raw material by weight in the final pellet by weight. If additives, impurities and / or water are present in the granular starting material in step (i), the term "weight %" includes the additives, impurities and / or water.
[0062] In order to make the present invention more easily understood, the present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0063] Figure 1 The results show the effect of moisture content on cold crush strength (CCS) of carboxymethyl cellulose.
[0064] Figure 2 Results of repeated CCS tests are shown. Pellets represented by black bars contain 0.5 wt% CMC added to a >68 wt% Fe concentrate without a pre-gelling step, and white bars contain 0.5 wt% CMC added to a >68 wt% Fe concentrate with a pre-gelling step, wherein the CMC is added to water and forms a hydrogel and then added to the >68 wt% Fe concentrate, according to the invention; and
[0065] Figure 3 The results of the effect of temperature change on CCS are shown for CMC. Example
[0066] Example 1 - Pellet Formation by Roller Pressing (Pre-gelation)
[0067] At 30°C, CMC powder was mixed with water at a ratio of 1 part CMC to 16 parts water until all the powder dissolved and a gel was produced. The temperature was maintained at 30°C. 600 g of the resulting organohydrogel binder was mixed with 7.5 kg of dry hematite > 65 wt% Fe iron ore (dried to constant mass at 105°C) in a high shear mixer at 45 rpm for 3 minutes. Sodium silicate was added and the mixture was then mixed for an additional 3 minutes. The resulting substrate mixture was formed into a mass using a Hutt roller press to produce oval rolled pellets (approximately 15 mm×26 mm×36 mm, 11.2 cm 3 ) and cured at 40° C. for 24 hours. The resulting pellets contained 0.25 wt % CMC and 2 wt % silicate.
[0068] Example 2 - Pellet Formation by Roller Pressing (Pre-gelation)
[0069] The method of Example 1 was repeated using magnetite iron ore with >68 wt% Fe (the moisture content of >68 wt% Fe was adjusted to 8% so that the total water content in the system was the same as that in Example 1).
[0070] Comparative Example 3 - Pellet Formation by Roller Pressing (Powder Binder)
[0071] The process of Example 1 was repeated using hematite iron ore but without gelation of the CMC before adding to the >65 wt% Fe iron ore (dried to constant mass at 105°C to provide pellets with the same moisture content as Example 1).
[0072] Comparative Example 4 - Pellet Formation by Roller Pressing (Powder Binder)
[0073] The method of Example 1 was repeated using magnetite iron ore, but without gelation of the CMC before adding to the >68 wt% Fe iron ore (the moisture content of the >68 wt% Fe was adjusted to 8% so that the total water content in the system was the same as that of Example 1).
[0074] Example 5 - Pellet formation by roller compaction (pre-gelation)
[0075] The process of Example 1 was repeated without the subsequent addition of sodium silicate, so that the resulting pellets contained 0.25 wt.% CMC.
[0076] Example 6 - CCS Test
[0077] The CCS of each of Example 1, Example 2 and Example 5 and Comparative Examples 3 and 4 was determined using a standard method according to ISO 4700:2015 using a Mecmesin Omnitest materials tester 10. The results are provided in Table 1 below.
[0078] Table 1
[0079] Example Adhesive used Substrate CCS(kgf) 1 CMC+Silicate Hematite 337 2 CMC+Silicate magnetite 478 3 CMC+Silicate Hematite (Comparison) 316 4 CMC+Silicate Magnetite (Comparison) 303 5 CMC Hematite 198
[0080] Table 1 clearly shows that in case the binder is gelled before addition to the substrate, the CCS is higher than using the comparative conventional technique. It is also observed that in case of using CMC alone, it is possible to prepare strong pellets with a CCS just below 200 kgf, a significant increase in strength over the typical values of non-gelled CMC which tend to fall in the range of 30 kgf to 50 kgf and tend to disintegrate. It is also observed that in case the moisture content of the substrate increases, this has a negative impact on the CCS. This is Figure 1 Shown in.
[0081] Example 7
[0082] Cylindrical pellets (approximately 16 mm diameter x 16 mm length, 3.2 cm 3 ) were subjected to CCS testing with pellets comprising 0.5 wt% CMC added to a >68 wt% Fe concentrate. The first sample type included a pre-gelling step and the second used conventional techniques. 10 different grades of CMC (from three different suppliers) were tested.
[0083] Results are available on Figure 2 In which different grades of CMC are compared under the same conditions. The black bars represent pellets formed without gelation of the CMC before addition to the >68 wt% Fe concentrate, and the white bars represent pellets formed with gelation of the CMC before addition to the >68 wt% Fe concentrate. Therefore, the data is roughly equivalent to the test data of Example 1 (with gelation) and Example 4 (without gelation).
[0084] like Figure 2 As shown in (where "strength" on the y-axis corresponds to CCS in kilonewtons (kN), where 1 kgf = 0.0098 kN), all cases in which pellets were formed with a gelation step (represented by white bars) showed improved CCS relative to pellets formed without a gelation step.
[0085] Example 8 - Temperature of gel formation (pre-gelation)
[0086] A series of experiments were conducted to determine the optimum solubilization temperature for an illustrative 30,000 molecular weight grade CMC as an organic binder. The CMC was treated by adding the powder to water at 20°C, 30°C, 40°C and 50°C in a weight ratio of 1:16 until a gel formed. The resulting gel was used in a standard recipe added as an 8% solution to magnetite iron ore >68 wt% Fe to produce cylindrical test pellets (approximately 16 mm diameter x 16 mm length, 3.2 cm 3 ), and tested its CCS according to ISO4700:2015 using Mecmesin Omnitest material tester 10. The results are shown in Figure 3 As can be seen, the optimum temperature for solubilization was found to be lower temperatures, for example in the range of 15°C to 35°C, with the highest intensity observed at 20°C or 30°C, with 30°C providing the best results.
[0087] Example 9 - Roller-Pellet Formation (In-Situ)
[0088] 0.3 wt% CMC was mixed with 7.5 kg of hematite >65 wt% Fe iron ore with a moisture content of 5.5% (wet iron ore) in a high shear mixer at 45 rpm for 3 minutes. The resulting wet substrate mixture was left at ambient temperature (in the range of 20°C to 25°C) for 1 hour to allow a hydrogel of the CMC to form around the iron ore. 2 wt% sodium silicate was added and the mixture was then mixed for an additional 3 minutes. The substrate mixture was then formed into agglomerates using a Hutt roller press to produce oval rolled pellets (approximately 15 mm x 26 mm x 36 mm, 11.2 cm 3 ), and cured at 40°C for 24 hours.
[0089] Example 10 - Roller-Pellet Formation (In-Situ)
[0090] The process of Example 9 was repeated using magnetite iron ore having >68 wt% Fe.
[0091] Comparative Example 11 - Pellet Formation by Roller Pressing (In-Situ)
[0092] The process of Example 9 was repeated using hematite > 65 wt% Fe iron ore, but without a resting phase and therefore without the formation of a hydrogel around the iron ore.
[0093] Comparative Example 12 - Pellet Formation by Roller Pressing (In Situ)
[0094] The process of Example 9 was repeated using a hematite magnetite iron ore having >68 wt% Fe, but without a resting stage and therefore without forming a hydrogel around the iron ore.
[0095] Example 13 - CCS and Tumble Index Test
[0096] The CCS and Tumble Index (TI) of each of Example 9, Example 10 and Comparative Examples 11 and 12 were determined using a Mecmesin Omnitest material tester 10 using standard methods and ISO 3271: 1995 according to ISO 4700: 2015, respectively. The results are provided in Table 2 below.
[0097] Table 2
[0098] Example Substrate CCS(kgf) TI 9 Hematite 450 90 10 magnetite 405 95 11 Hematite (Comparison) 334 85 12 Magnetite (Comparison) 303 88
[0099] Table 2 clearly shows that when the binder and substrate mixture is allowed to stand to form a gel, the CCS is higher than that of the conventional technique using the comparison. In addition, the tumbling index of the sample is higher, indicating that a more solid pellet is formed. The industrial standard for TI is in the range of 90 to 95, and Examples 9 and 10 meet the industrial standard, while Comparative Examples 11 and 12 do not meet the industrial standard.
[0100] Example 14 - Roller-Pellet Formation (In-Situ)
[0101] 0.5 wt% polyacrylamide (two different grades) was mixed with 7.5 kg of magnetite iron ore (>68 wt% Fe) having a moisture content of 5.5% (wet iron ore) in a high shear mixer at 45 rpm for 3 minutes. The resulting wet substrate mixture was left at ambient temperature (in the range of 20°C to 25°C) for the time shown in Table 3 below to allow a hydrogel of the polyacrylamide to form around the iron ore. In some examples, 2.0 wt% sodium silicate was added and the mixture was then mixed for an additional 3 minutes. The substrate mixture was then formed into lumps using a Hutt roller press to produce "square" rolled pellets (approximately 15 mm x 26 mm x 36 mm, 2.5 cm 3 ), and cured at 40°C for 24 hours.
[0102] Table 3
[0103]
[0104] As can be seen, for both the individual polyacrylamide and silicate / polyacrylamide systems, higher strengths are generally observed with standing, and improvements can be observed with as little as 30 minutes of standing time. However, when silicate is not present, polyacrylamide requires a longer time to form a strong bond (values in excess of 60 for use without disintegration), up to one day. It is often the case that the presence of silicate significantly increases strength relative to individual polyacrylamide, indicating the benefit of the auxiliary binder of the present invention.
[0105] Example 15 - Roller-Pellet Formation (In-Situ)
[0106] The method of Example 14 was repeated using 0.5 wt% polyvinyl alcohol and 0.5 wt% phenolic resin, wherein the polyvinyl alcohol was provided in dry form. The results are shown in Table 4 below.
[0107] Table 4
[0108]
[0109]
[0110] As can be seen, relative to the case where no gel is formed, the strength increases significantly with gel formation (from 26 kgf to 65 kgf for PVA alone, and from 20 kgf to 103 kgf for PVA+phenolic resin). At a strength of 20 kgf, pellets can be formed, but will not remain intact. The gelling step enables the formation of stable pellets using PVA alone, and the combination of PVA and phenolic resin provides additional strength.
[0111] Similar results were achieved when the polyvinyl alcohol was provided in liquid form.
[0112] It will be appreciated that the methods and apparatus of the present invention can be implemented in a variety of ways, only a few of which have been illustrated and described above.
Claims
1. A method for producing pellets, the method comprising the following steps: a. mixing an organic binder with water to form an organic hydrogel binder; b. mixing the hydrogel with a particulate substrate selected from metal ore, waste containing metal ore, metal fines, iron slag, iron filings, mineral waste, carbonaceous material, electric arc furnace waste or a combination thereof to form a substrate mixture; and c. Forming clumps.
2. A method for producing pellets, the method comprising the following steps: a. providing a wet particulate substrate selected from metal ore, waste containing metal ore, metal fines, iron slag, iron filings, mineral waste, carbonaceous material, electric arc furnace waste or a combination thereof; b. mixing the wet granular substrate with an organic binder to form a wet substrate mixture; c. allowing the wet substrate mixture to stand so that a hydrogel of the organic binder is formed around the particle substrate; and d. Form clumps.
3. The method of claim 1 or 2, wherein the particle substrate comprises a metal.
4. A method according to any preceding claim, wherein the particulate substrate comprises iron.
5. The method of any preceding claim, wherein the particulate substrate is added in an amount of about 70% to about 99.9% by weight of the pellets.
6. A method according to any preceding claim, wherein the organic binder is selected from organic resins, cellulosic materials, polyvinyl alcohol, phenolic resins and / or polysaccharides.
7. The method of claim 6, wherein the organic binder comprises carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), or a combination thereof.
8. The method of any preceding claim, wherein the organic binder is added in an amount of about 0.05% to about 1.5% by weight of the pellets.
9. A method according to any preceding claim, further comprising the step of adding a supplementary binder to the substrate mixture.
10. The method of claim 9, wherein the auxiliary binder comprises an inorganic binder.
11. The method of claim 10, wherein the inorganic binder comprises one or more silicates, or refractory materials comprising oxides, carbides, or nitrides of silicon, aluminum, magnesium, calcium, and zirconium, and combinations thereof.
12. The method of claim 11, wherein the inorganic binder comprises one or more silicates.
13. The method according to any one of claims 9 to 12, wherein the auxiliary binder is in powder form.
14. The method of any one of claims 9 to 13, wherein the auxiliary binder is added in an amount of about 0.5% to about 2.5% by weight of the substrate mixture.
15. A method according to any preceding claim further comprising the step of adding a separate processing aid to the substrate mixture.
16. The method of any one of claims 1 and 3 to 15, wherein the organohydrogel binder is formed at a temperature in the range of about 10°C to about 60°C.
17. A method according to any preceding claim, wherein the step of forming the pellets comprises extruding the mass.
18. A method according to any preceding claim, wherein the step of forming the pellets comprises heating the agglomerates to a temperature in the range 10°C to 250°C.
19. The method of any one of claims 2 to 15, claim 17 and claim 18, wherein the wet particulate substrate comprises water in the range of about 1 wt% to about 40 wt%.
20. A pellet obtained by the process of any preceding claim, comprising a particulate substrate selected from metal ore, waste containing metal ore, metal fines, iron slag, iron filings, mineral waste, carbonaceous material, electric arc furnace waste or a combination thereof and an organic hydrogel binder.
21. The pellets of claim 20, wherein the pellets are heated to a temperature in the range of 10°C to 250°C.